The Experience of Pregnant Women Following Prenatal Gentle Yoga: Scoping Review - Migita Vidia Amita ,Sri Ratnaningsih (International Journal of Advanced Science and Technology, 2020)
During pregnancy, pregnant women will experience change physically and psychologically. Prenatal gentle yoga is one of ways for pregnant women to be relaxed and clam in facing of second and third trimester pregnancy. The objective of the study is to review the evidence related to the experience of pregnant women following prenatal gentle yoga. Scoping review adopted from Arskey and O’Malley framework using original articles published between 2009 and 2019 from database sources namely Wiley Online Library, PubMed, and Science Direct. From 693 articles, there were 20 articles which fulfill inclusion criteria and conducted critical appraisal using Joanna Brigs Institute tools. Based on the articles can be obtained that the research design is randomized controlled trial of 12 articles, six articles of quasi experiment, a cross-sectional design article, and qualitative research of focus group discussion article. There are 4 theme mappings, namely the benefits of prenatal gentle yoga for physical health of pregnant women, the benefits of prenatal gentle yoga for psychic pregnant women, the benefits of prenatal gentle yoga in the birth process, and the benefits of prenatal gentle yoga for the fetus. Prenatal gentle yoga class is not only for pregnant women but also the involvement of husband can improve mental health and confidence in pregnant women.